ANALISIS FAKTOR PENYEBAB BERALIHNYA MASYARAKAT DALAM PENGGUNAAN SUMUR GALIAN MENJADI SUMUR BOR DI KECAMATAN BARUMUN KABUPATEN PADANG LAWAS - Hasibuan, Hadomuan; Harefa, Meilinda Suriani (Program Studi Pendidikan Geografi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Samudra, 2025)
This research investigates the reasons why people in Barumun District, Padang Lawas Regency, are switching from hand-dug wells to boreholes. Conducted in November 2023, the study used a qualitative approach, employing observations, questionnaires, and interviews with residents who have already made the switch. The findings reveal several key drivers for this change. Firstly, there is a desire for easier, faster, and more energy-efficient access to groundwater. Secondly, safety concerns, such as livestock falling into the hand-dug wells, play a significant role. Thirdly, the decline in groundwater levels has caused many hand-dug wells to dry up and become unreachable. The community perceives that replacing dry hand-dug wells with boreholes is an effective solution. Consequently, the role of hand-dug wells in the community has significantly diminished, with many no longer being used.